2018
DOI: 10.1016/j.nima.2018.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a GridPix detector based on the Timepix3 chip

Abstract: With the ultimate goal of developing a pixel-based readout for a TPC at the ILC, a GridPix readout system consisting of one Timepix3 chip with an integrated amplification grid was embedded in a prototype detector. The performance was studied in a testbeam with 2.5 GeV electrons at the ELSA accelerator in Bonn. The error on the track position measurement both in the drift direction and in the readout plane is dominated by diffusion. Systematic uncertainties are limited to below 10 µm. The GridPix can detect sin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 11 publications
(16 reference statements)
1
16
0
Order By: Relevance
“…The quad module was embedded in a TPC detector and operated at the ELSA test beam facility. The single electron resolutions in the transverse and longitudinal planes are similar to the results obtained for the single-chip detector [5] and primarily limited by diffusion. It is shown that a systematic error from the quad detector for the distortions over the pixel plane of 13 µm (9 µm in the central region) has been achieved.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The quad module was embedded in a TPC detector and operated at the ELSA test beam facility. The single electron resolutions in the transverse and longitudinal planes are similar to the results obtained for the single-chip detector [5] and primarily limited by diffusion. It is shown that a systematic error from the quad detector for the distortions over the pixel plane of 13 µm (9 µm in the central region) has been achieved.…”
Section: Discussionsupporting
confidence: 78%
“…This newer chip offers superior timing, faster readout speed and the possibility to apply time walk corrections. The first results of a single chip detector have been analysed and published in [5]. Electron diffusion in gas was found to be the dominant error on the track position measurement and systematics in the pixel plane remained below 10 µm.…”
Section: Introductionmentioning
confidence: 99%
“…If we assume 220 for n 0 23 the estimated values of F and f are 0.20 ± 0.08 and 0.84 ± 0.06, respectively. It should be noted, however, that the values of F and f quoted above are preliminary since the average number of primary electrons ( n 0 ) is not exactly known for the Penning gas mixture used 24 . Possible increase in the value of n 0 makes F (f ) smaller (larger).…”
Section: Discussionmentioning
confidence: 98%
“…It is essentially a precisely aligned double-mesh layer with an embedded insulating spacer in-between, to be referred to as the gating foil hereafter in the present paper. The gating foil with a frame can be mounted on top of the amplification GEM stack or Micromegas, with either ordinary pad readout or pixel readout [23,24], just like an additional ordinary GEM foil, thereby realizing a wire-less gas amplification device for TPCs with ion-blocking capability 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation